Increases in Network Ties Are Associated With Increased Cohesion Among Intervention Participants. (April 2016) - Gesell, Sabina B.; Barkin, Shari L.; Sommer, Evan C.; Thompson, Jessica R.; Valente, Thomas W.
Objective . Many behavior change programs are delivered in group settings to manage implementation costs and to foster support and interactions among group members in order to facilitate behavior change. Understanding the group dynamics that evolve in group settings (e.g., weight management, Alcoholics Anonymous) is important, yet rarely measured. This article examined the relationship between social network ties and group cohesion in a group-based intervention to prevent obesity in children. Method . The data reported are process measures from an ongoing community-based randomized controlled trial. A total of 305 parents with a child (3-6 years) at risk of developing obesity were assigned to an intervention that taught parents healthy lifestyles. Parents met weekly for 12 weeks in small consistent groups. Two measures were collected at Weeks 3 and 6: a social network survey (people in the group with whom one discusses healthy lifestyles) and the validated Perceived Cohesion Scale. We used lagged random and fixed effects regression models to analyze the data. Results . Cohesion increased from 6.51 to 6.71 ( t = 4.4, p < .01). Network nominations tended to increase over the 3-week period in each network. In the combined discussion and advice network, the number of nominations increased from 1.76 to 1.95 ( z = 2.59, p < .01). Cohesion at Week 3 was the strongest predictor of cohesion at Week 6 ( b = 0.55, p < .01). Number of new network nominations at Week 6 was positively related to cohesion at Week 6 ( b = 0.06, p < .01). In sum, being able to name new network contacts was associated with feelings of cohesion. Conclusion . This is the first study to demonstrate how network changes affect perceived group cohesion within a behavioral intervention. Given that many behavioral interventions occur in group settings, intentionally building new social networks could be promising to augment desired outcomes.